Glycemic-dependent changes of skin autofluorescence level in children and adolescents with type 1 diabetes mellitus - M. V. Proskurina; N. G. Kiseleva; V. V. Salmin; T. E. Taranushenko (Бюллетень сибирской медицины)
Aim. To study the effect of glycated hemoglobin level, average daily glycemia and its variability on UV-induced skin autofluorescence in children and adolescents with type 1 diabetes.Materials and methods. The study included 47 children and adolescents with type 1 diabetes living in a restrictedaccess administrative and territorial unit. The autofluorescence spectra of the skin from the inner surface of the shoulder and nails of patients were recorded using an original compact spectrofluorometer based on STS-VIS OCEAN OPTICS © USA microspectrometer with UVA excitation. The statistical analysis was performed using Statsoft Statistica 12.0 software. The fluorescence spectra were normalized to the average value of the UV LED signal and the moving average smoothed using a 10 nm window. Then, the renormalization of spectra was carried out, minimizing their spread from the average sample spectrum.Results. The study revealed the most changeable regions of UV-induced skin autofluorescence spectrum with variations in the level of glycated hemoglobin, average daily glycemia, and glycemic variability.Conclusion. The study confirms the prospects of using skin autofluorescence measurements as a non-invasive tool for assessing the state of carbohydrate metabolism.